Cefuroxime-Loaded Hydrogels for Prevention and Treatment of Bacterial Contamination of Open Wounds - Pavlo Virych (Hindawi Limited, 2021)
Dextran/Sulfodextran-graft-polyacrylamide- and polyacrylamide-based hydrogels were synthesized by radical polymerization and loaded with cefuroxime to obtain antimicrobial wound dressings. Antibiotic release from the antibiotic-loaded hydrogels into an aqueous solution was studied by the HPLC-UV method. It is shown that cefuroxime-loaded Dextran/Sulfodextran-graft-polyacrylamide hydrogels release the antibiotic more slowly compared to polyacrylamide hydrogel with the same density of cross-links. Antibacterial activity of the synthesized materials was tested in vitro against wild strains of S. aureus, E. coli, and Klebsiella spp. The possibility of using the obtained antimicrobial hydrogels for the treatment of infected wounds was confirmed in vivo in a rat model.